Impaired memory and learning abilities in patients with systemic lupus erythematosus as measured by the Rey Auditory Verbal Learning Test. Issue 6 (1st July 2008) - Paran, D; Litinsky, I; Shapira-Lichter, I; Navon, S; Hendler, T; Caspi, D; Vakil, E
Abstract : Objective: The purpose of this study was to assess and characterise verbal memory impairment in patients with systemic lupus erythematosus (SLE) by the Rey Auditory Verbal Learning Test (Rey AVLT). Methods: 40 consecutive, unselected patients with SLE were evaluated with the Rey AVLT, a clinical and research tool for the study of multiple learning and memory measures. All patients were assessed for disease activity, damage, presence of antiphospholipid antibodies and depression. Findings were compared with those of 40 healthy controls matched for age, sex and education. Results: The study group included 40 patients with SLE (37 females, 3 males), median age 33 years (range 20–59), median disease duration 8 years (range 0.3–32). The median disease activity measured by the SLE Disease Activity Index (SLEDAI) was 4 (range 0–16). Median damage measured by the SLICC/ACR (Systemic Lupus International Collaborating Clinics/American College of Rheumatology) damage index score was 0 (range 0–4). Depression was detected in 16/40 patients. Several aspects of the memory domain, as measured by the Rey AVLT, were impaired in the SLE group, using analysis of variance with repeated measures. The learning curve of patients with SLE was significantly less steep compared with that of controls, (p = 0.036), the rate of words omitted from trial to trial was higher in the SLE group (p = 0.034) and retrieval was less efficient in SLE compared with controls (p = 0.004). The significance of these findings was maintained after omitting patients with stroke or depression. Conclusion: Learning ability was impaired in patients with SLE with a poor and inefficient learning strategy, as reflected by an impaired learning curve, repeated omissions and impaired retrieval. This pattern of memory deficit resembles that seen in patients with frontal lobe damage and warrants further localising brain studies.